Above-ground Space Utilization and Feeding Guild of Tropical Rainforest Birds in Sarawak, Borneo - Pang, Sing Tyan; Attiqqah Fadziliah, Sapian; Khatijah, Ismail; Andrew Alek, Tuen (Transactions on Science and Technology, 2017)
Above-ground space within tropical rainforests harbour many bird species. However, the mechanism for their coexistence remains largely unknown. Avian feeding guilds are known to be good indicator of habitat specialization, but the details of how bird use of above-ground space, especially in reference to feeding remain unclear. Double-stacked mist-nets, with a total of six shelves and extending up to 3.6 metres above ground, were deployed at 30 forest sites in the Baram, Baleh and Pelagus regions of Sarawak, Borneo (East Malaysia). A total of 2,613 birds, comprising 124 species, were captured. Eight feeding guilds were identified, with insectivores being the most abundant. Most birds were captured at shelf 3 and 4, equivalent to 1.2 to 2.4 metres above-ground. Both the number of species and individuals captured in the shelves increased from the ground upwards to reach a maximum at shelf 3, after which it decreased. Insectivores were the most common guilds at the lowest two shelves, accounting for 68 % in shelf 1 and 47 % in shelf 2. This study shows that tropical forest birds are able to coexist in the relative safety of the above-ground space by exploiting different food resources indicating the importance of feeding guild in determining vertical stratification of avifauna species.